The Oral Health of School Children in the Ho Municipality, Ghana - TUOSIE BENI, P (University of Ghana, 2009)
An exploratory oral health study was undertaken in the Ho Municipality, Ghana in order to determine the prevalence of oral diseases among school children and provide baseline data on their oral health. The knowledge and practices among the school children with respect to oral cleaning practices and oral health seeking behaviour, and the eating habits associated with oral health problems were determined.
Keywords: ORAL HEALTH; SCHOOL; CHILDREN; HO MUNICIPALITY